A method to estimate crop effects at higher frequencies by modeling and microwave radiometric data - Zhang, ZhongJun; Zhang, LiXin; Sun, GuoQing; Liu, QinHuo (Science China. Earth sciences, 2012)
To use the 0th-order τ-ω model to retrieve soil moisture from radiometric data at frequencies higher than the C band, the characteristics of the effective single scattering albedo ω and the opacity rof vegetation must be studied. In this paper, the co and r values of corn for the C, X, and Ku bands were retrieved by matching the simulations of a high-order matrix-doubling model to the τ-ω model. First, the brightness temperature of the matrix-doubling was validated by a truck-mounted radiometer in a field experiment, where the vegetation emission contributions were validated with aluminum foil to mask the soil emission. Then an emissivity database of corn fields for different growing seasons was established for a variety of soil conditions. With the transmissivity of corn determined from the database, the effective single scattering albedos of corn for different heights at the C, X, and Ku bands and at a 55° viewing angle were derived. To verify the accuracy of the derived co and τ values, we used SMEX02/PSR aircraft data and the Qp model to retrieve the soil moisture; the RMSE between the retrieval and the measurements was 4.76% at the C band and 5.36% at the X band.